WN-2-Absorbing Submodules And WNS-2-Absorbing Submodules - Hussain, Wissam A.; Mohammd ali, Haibt K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In’’this"article, we"study",the"concept""of WN"-"2"-’’Absorbing’’’submodules and WNS’’-’’2’’-’’Absorbing"submodules as generalization of "weakly 2-absorbing and weakly semi 2-absorbing submodules respectively. We investigate some of basic properties, examples and characterizations of them. Also, prove, the class of WN-2-Absorbing "submodules is contained in the class of WNS-2-Absorbing "submodules. Moreover, many interesting results about these concepts, were proven.